Molecular models of protein kinase 6 from Plasmodium falciparum - Manhani, K. K.; Arcuri, H. A.; da Silveira, NJF; Uchoa, H. B.; de Azevedo, W. F.; Canduri, F. (Springer, 2005)
Cyclin-dependent kinases (CDKs) have been identified as potential targets for development of drugs, mainly against cancer. These studies generated a vast library of chemical inhibitors of CDKs, and some of these molecules can also inhibit kinases identified in the Plasmodium falciparum genome. Here we describe structural models for Protein Kinase 6 from P. falciparum (PfPK6) complexed with Roscovitine and Olomoucine. These models show clear structural evidence for differences observed in the inhibition, and may help designing inhibitors for PfPK6 generating new potential drugs against malaria.
Keywords: kinases; bioinformatics; Plasmodium falciparum; Roscovitine; Olomoucine